The association between attention-deficit/hyperactivity disorder and Atopic dermatitis: A study among Iranian children - Najmolsadat Atefi; Masoumeh Rohaninasab; Mitra Shooshtari; Elham Behrangi; Golnaz Mehran; Azade Goodarzi; Sadaf Sajedi Moghadam; Safoura Shakoei (Wolters Kluwer Medknow Publications, 2019)
Background: The co-occurrence of attention-deficit/hyperactivity disorder (ADHD) with atopic dermatitis (AD) has been well described in some recent association studies; however, we did not have any perspective on this relationship in our country. Aim and Objective: Hence, the present study aimed to assess the prevalence of ADHD in children with AD. Materials and Methods: This cross-sectional study was performed on 95 consecutive children and adolescents (aged 4-18 years) who were referred to dermatology clinics at the two hospitals in Tehran during 2017 with atopic dermatitis. The evidence of atopy was assessed using the 2003 National Survey of Children's Health. The diagnosis of ADHD was based on the Conner Rating Scale. The sleep disorder was also assessed by the Pittsburg sleep quality questionnaire. Results: The prevalence of hyperactivity and attention deficit in our AD patients was 20.0% and 29.47%, respectively. Furthermore, patients with sleep problem were significantly more likely to have hyperactivity disorder (odds ratio [OR]: 2.91, 95% confidence interval [CI]: 1.04-8.16, P = 0.04). According to the results of multiple logistic regression analyses, flexor involvement was the only predictor of hyperactivity disorder in the final model. The univariate and multivariate analyses showed that having attention deficit was associated with having cheek involvement (OR = 3.63, 95% CI: 1.44-9.14, P = 0.01) and sleep problem (OR = 3.68, 95% CI: 1.45-9.33, P = 0.01). Conclusion: It seems that neurocognitive disturbances due to sleep restriction in AD children may be one of the main trigger, especially for attention deficit.